Cardiac Biomarkers of High Risk of Complications and Death in Patients with SARS-COV-2 and CHF - Yuliya Olegovna Glavatskikh, Andrey Valerievich Budnevsky, Roman Evgenyevich Tokmachev, Natalia Evgenyevna Nekhaenko, Evgeny Viktorovich Tokmachev, Arina Anatolievna Kupriyanova, Igor Evgenyevich Pomogaibo, (Pakistan Journal of Medical & Health Sciences, 2022)
The review is devoted to investigate cardiovascular biomarkers in patients with SARS-CoV-2 associated with a high risk of complications and death. The article provides information on the main cardiovascular biomarkers and pro-inflammatory cytokines in relations to the processes of decompensation in patients with chronic heart failure complicated by ARVI, including the SARS-CoV-2. MeSHwords: heart failure, troponin I, NT-proBNP, cytokines, SARS-CoV-2